An anti-ErbB2 fully human antibody circumvents trastuzumab resistance - Lu, Qiong (Oncotarget, 2016)
Trastuzumab, an anti-HER2/ErbB2 humanized antibody, has shown great clinical benefits in ErbB2-positive breast cancer treatment. Despite of its effectiveness, response rate to trastuzumab is limited and resistance is common. Here, we developed a new anti-ErbB2 antibody, denoted as H2-18, which was isolated from a phage display human antibody library. Previous studies have demonstrated that trastuzumab recognizes the juxtamembrane region of domain IV, and pertuzumab, another humanized ErbB2-specific antibody, binds to ErbB2 near the center of domain II. Our crystallographic analysis showed that the epitope recognized by H2-18 is within domain I of the ErbB2 molecule. H2-18 potently induced programmed cell death (PCD) in both trastuzumab-sensitive and -resistant breast cancer cell lines, while trastuzumab and pertuzumab, either used alone or in combination, only exhibits very weak PCD-inducing activity. More importantly, H2-18 could inhibit the growth of trastuzumab-resistant breast cancer cells far more effectively than trastuzumab plus pertuzumab, both in vitro and in vivo. In conclusion, H2-18 shows a unique ability to overcome trastuzumab resistance, suggesting that it has the great potential to be translated to the clinic.